Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Let's analyze the given expression and rewrite it in the form [tex]\( (x + c)^2 + d \)[/tex].
### Part (a) Completing the square
To complete the square for the expression [tex]\( x^2 + 6x + 11 \)[/tex]:
1. Start with the quadratic expression:
[tex]\[ x^2 + 6x + 11 \][/tex]
2. Take the coefficient of [tex]\( x \)[/tex], which is 6, divide it by 2 and square it:
[tex]\[ \left(\frac{6}{2}\right)^2 = 3^2 = 9 \][/tex]
3. Add and subtract this squared value inside the expression:
[tex]\[ x^2 + 6x + 9 + 11 - 9 \][/tex]
4. Now, rewrite the quadratic and the perfect square trinomial:
[tex]\[ (x^2 + 6x + 9) + 2 = (x + 3)^2 + 2 \][/tex]
So, the expression [tex]\( x^2 + 6x + 11 \)[/tex] can be written as [tex]\( (x + 3)^2 + 2 \)[/tex].
Thus, we have:
[tex]\[ c = 3 \quad \text{and} \quad d = 2 \][/tex]
### Part (b) Finding the coordinates of the turning point
The turning point (or vertex) of the quadratic function [tex]\( y = x^2 + 6x + 11 \)[/tex] is the minimum point of the parabola described by the expression [tex]\( (x + 3)^2 + 2 \)[/tex].
The expression in the form [tex]\( (x + 3)^2 + 2 \)[/tex] reveals that the quadratic achieves its minimum value when the squared term [tex]\( (x + 3)^2 \)[/tex] is zero. This happens when [tex]\( x = -3 \)[/tex].
- At [tex]\( x = -3 \)[/tex]:
[tex]\[ y = (x + 3)^2 + 2 = (0)^2 + 2 = 2 \][/tex]
Therefore, the turning point of the curve [tex]\( y = x^2 + 6x + 11 \)[/tex] is:
[tex]\[ (-3, 2) \][/tex]
### Summary
(a) The expression [tex]\( x^2 + 6x + 11 \)[/tex] can be written as [tex]\( (x + 3)^2 + 2 \)[/tex] with [tex]\( c = 3 \)[/tex] and [tex]\( d = 2 \)[/tex].
(b) The coordinates of the turning point of the curve [tex]\( y = x^2 + 6x + 11 \)[/tex] are [tex]\( (-3, 2) \)[/tex].
### Part (a) Completing the square
To complete the square for the expression [tex]\( x^2 + 6x + 11 \)[/tex]:
1. Start with the quadratic expression:
[tex]\[ x^2 + 6x + 11 \][/tex]
2. Take the coefficient of [tex]\( x \)[/tex], which is 6, divide it by 2 and square it:
[tex]\[ \left(\frac{6}{2}\right)^2 = 3^2 = 9 \][/tex]
3. Add and subtract this squared value inside the expression:
[tex]\[ x^2 + 6x + 9 + 11 - 9 \][/tex]
4. Now, rewrite the quadratic and the perfect square trinomial:
[tex]\[ (x^2 + 6x + 9) + 2 = (x + 3)^2 + 2 \][/tex]
So, the expression [tex]\( x^2 + 6x + 11 \)[/tex] can be written as [tex]\( (x + 3)^2 + 2 \)[/tex].
Thus, we have:
[tex]\[ c = 3 \quad \text{and} \quad d = 2 \][/tex]
### Part (b) Finding the coordinates of the turning point
The turning point (or vertex) of the quadratic function [tex]\( y = x^2 + 6x + 11 \)[/tex] is the minimum point of the parabola described by the expression [tex]\( (x + 3)^2 + 2 \)[/tex].
The expression in the form [tex]\( (x + 3)^2 + 2 \)[/tex] reveals that the quadratic achieves its minimum value when the squared term [tex]\( (x + 3)^2 \)[/tex] is zero. This happens when [tex]\( x = -3 \)[/tex].
- At [tex]\( x = -3 \)[/tex]:
[tex]\[ y = (x + 3)^2 + 2 = (0)^2 + 2 = 2 \][/tex]
Therefore, the turning point of the curve [tex]\( y = x^2 + 6x + 11 \)[/tex] is:
[tex]\[ (-3, 2) \][/tex]
### Summary
(a) The expression [tex]\( x^2 + 6x + 11 \)[/tex] can be written as [tex]\( (x + 3)^2 + 2 \)[/tex] with [tex]\( c = 3 \)[/tex] and [tex]\( d = 2 \)[/tex].
(b) The coordinates of the turning point of the curve [tex]\( y = x^2 + 6x + 11 \)[/tex] are [tex]\( (-3, 2) \)[/tex].
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.